Sitting in the Room with Glissant Imagining, Relating, and Translating the World - Srivastava, Devarya (eCahiers de l'Institut, 2023)
Existing in deep relation with the work of poet, philosopher, and theorist Édouard Glissant, this paper, taking as its grounding the Caribbean archipelago, explores ways of thinking/being/imagining/inhabiting the world as constituted in and through relations of multiplicity. The pages that follow take up this task through a series of philosophies co- constituted in dialogue with Glissant. Reading Glissant generatively (albeit, at times errantly) through the optic of 'translations', this paper takes up the 'big' questions confronting political philosophy, such as, 'thinking', 'being', 'freedom', 'difference', 'space', and 'time'. Suggesting that these questions can be usefully approached from the tortured landscape of the Caribbean, this paper makes the case for orienting critical inquiry and political action around modalities of relationality, multiplicity, and non-systematicity. In doing so, this paper puts forward a poetic mode of critique, which, while thinking through the world- breaking historical violence instituted by coloniality, slavery, and other dispossessions, is immanently able to overcome them through an affirmative, de-territorialised, and inventive ethico-political stance.